THE EFECT OF IMPLEMENTATION OF ACCOUNTING INFORMATION SYSTEM AND CONTROL ENVIRONTMENT ON THE EFFECTIVENESS OF INTERNAL CONTROL OF SALES AT CV. KURNIA AGUNG (CASE STUDY AT CV. KURNIA AGUNG REGIONAL JAWA BARAT) - Rosi Mika Aditya Mustopa; Indah Umiyati; Trisandi Eka Putri (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2019)
The purpose of this study to determine the effect of the implementation of accounting information systems and control environment to the effectiveness of internal control sales on the CV. Kurnia Agung. In this study was prepared using quantitative research methods, while the data analysis techniques in this study using descriptive data analysis techniques. Population and sample in this research is all employee CV. Kurnia Agung with 65 respondents with sample selection technique using purposive sampling method. The data used are primary data obtained directly from all employees CV. Kurnia Agung by distributing questionnaires. Data were analyzed using multiple linier regression method and hypothesis test with the help of using Statistical Program for Society Science (SPSS) V. 21. Based on the results of hypothesis testing in this study is the accounting information system affect the effectiveness of internal control sales, control environment affect the effectiveness of internal control sales, and accounting information systems and control environment simultaneously affect the effectiveness of internal control sales